2020
DOI: 10.1080/15592324.2020.1780038
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a female gametophyte defect in sdk1-7 +/- abi3-6 +/- heterozygotes of Arabidopsis thaliana

Abstract: Successful reproduction in angiosperms is dependent on the highly synchronous development of their male and female gametophytes and the ensuing fusion of the gametes from these reproductive tissue types. When crossing a T-DNA insertion line sdk1-7-/-(Salk_024564), one of the S-domain receptor kinases involved in ABA responses with a fast neutron deletion line abi3-6-/-, the F1 heterozygotes (sdk1-7+/-abi3-6 +/-) displayed 50% ovule abortion suggesting a likely gametophytic defects. We identified and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Regarding JA, it has been shown that JA regulates stamen development in Arabidopsis but also late ovule development and fertility in tomato through the function of MYC2/JAI1 (Schubert et al 2019;Huang et al 2023). In the case of ABA, it was reported a high ovule abortion in F1 plants from the cross of sdk1-7, one of the S-domain receptor kinases involved in ABA responses, with a null abi3-6 (Sankaranarayanan et al 2020). A more detailed analysis is the specific role of these hormones, and other plant growth regulators in ovule development would be crucial to better understand the complex hormonal network governing ovule primordia emergence.…”
Section: Other Hormones Involved On Ovule Initiationmentioning
confidence: 99%
“…Regarding JA, it has been shown that JA regulates stamen development in Arabidopsis but also late ovule development and fertility in tomato through the function of MYC2/JAI1 (Schubert et al 2019;Huang et al 2023). In the case of ABA, it was reported a high ovule abortion in F1 plants from the cross of sdk1-7, one of the S-domain receptor kinases involved in ABA responses, with a null abi3-6 (Sankaranarayanan et al 2020). A more detailed analysis is the specific role of these hormones, and other plant growth regulators in ovule development would be crucial to better understand the complex hormonal network governing ovule primordia emergence.…”
Section: Other Hormones Involved On Ovule Initiationmentioning
confidence: 99%